Tata Kelola Risiko di Era Kecerdasan Buatan: Tantangan dan Peluang Penerapan Manajemen Risiko Perusahaan dalam Transformasi Digital - Bolivia Renata Sianipar; Merlindang Simamora (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
Advances in artificial intelligence have fundamentally altered the organizational risk landscape. This study analyzed the evolution of risk governance in the artificial intelligence era through a systematic literature review of literature from two thousand twenty-one to two thousand twenty-five. Data were collected from indexed journals, consultant reports, and international standard frameworks. The results indicated a duality of artificial intelligence: as an enabler that transformed enterprise risk management into predictive, and as a source of new risks such as algorithmic bias and cyber vulnerability. Effective risk governance required reconstruction of three pillars: governance structure with artificial intelligence ethics committees, human-machine collaborative risk culture, and adaptive frameworks integrating artificial intelligence risk taxonomy. The conclusion emphasized that this transformation was a paradigmatic transformation requiring fundamental reconstruction in how organizations managed risk.